Study on Compliant Operation for Underwater Manipulator with Model Reference Adaptive Impedance Control - LI Shasha; XIA Manjiang; ZHANG Jianjun (Kongzhi Yu Xinxi Jishu)
To address challenges posed by model uncertainties due to joint friction and imprecise measurements faced by underwater manipulators during diverse operating missions, this paper proposes a model reference adaptive impedance control method aimed at enhancing robustness and operational stability. First, a desired impedance model based on the errors between the standard force and the operating force was developed. Adaptive laws and a bounded-gain-forgetting adaptive update strategy were formulated based on the operational spatial position and the desired position output from the impedance model, enabling the manipulator's end-effector to precisely track standard force signals. Then, a Lyapunov function was established, proving the global stability and force-position tracking performance of the system. Finally, a two-degree-of-freedom manipulator simulation experiment was conducted on the Matlab/Simulink platform. The results demonstrate that the proposed controller exhibits excellent adaptive performance and robustness, ensuring superior force-position tracking capabilities.